Development Design of Millennial Road Safety Festival Program in North Sulawesi Regional Police - Vita Mayastinasari; Benyamin Lufpi (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
One of the current programs to realize security, safety, order, and smooth traffic is the Millennial Road Safety Festival (MRSF). The focuses of problems in this research are respondents' views on